Metabolic Reprograming of Cystic Fibrosis Macrophages via the IRE1α Arm of the Unfolded Protein Response Results in Exacerbated Inflammation - Lara-Reyna, Samuel; Scambler, Thomas; Holbrook, Jonathan; Wong, Chi; Jarosz-Griffiths, Heledd H.; Martinon, Fabio; Savic, Sinisa; Peckham, Daniel; McDermott, Michael F. (Frontiers in Immunology, 2019)
Cystic Fibrosis (CF) is a recessive genetic disorder caused by mutations in the cystic fibrosis transmembrane conductance regulator (CFTR). CFTR mutations cause dysregulation of channel function with intracellular accumulation of misfolded proteins and endoplasmic reticulum (ER) stress, with activation of the IRE1-XBP1 pathway that regulates a subset of unfolded protein response (UPR) genes. This pathway regulates a group of genes that control proinflammatory and metabolic responses in different immune cells; however, the metabolic state of immune cells and this pathway’s role in CF remain elusive. Our results indicate that only innate immune cells from CF patients present increased levels of ER stress, mainly affecting neutrophils, monocytes and macrophages. An overactive IRE1-XBP1 pathway reprograms CF M1 macrophages towards an increased metabolic state, with increased glycolytic rates and mitochondrial function, associated with exaggerated production of TNF and IL-6. This hyper-metabolic state, seen in CF macrophages, is reversed by inhibiting the RNase domain of IRE1, thereby decreasing the increased glycolic rates, mitochondrial function and inflammation. Altogether, our results indicate that innate immune cells from CF patients are primarily affected by ER stress. Moreover, the IRE1-XBP1 pathway of the UPR is responsible for the hyper-metabolic state seen in CF macrophages, which is associated with the exaggerated inflammatory response. Modulating ER stress, metabolism and inflammation, by targeting IRE1, may improve the metabolic fitness of macrophages and other immune cells in CF and other immune-related disorders.